Could low Safety Attitudes Questionnaire scores be indicative of an environment where it may be difficult to get new training practices established?. (2nd January 2017) - Channing, Sarah; Ryan, Neil; Barnes, Sophie; Collins, Kate; van der Nelson, Helen; Mears, Jane; Siassakos, Dimitrios
Abstract : Introduction: Simulation-based, multiprofessional team training (SBMPTT) is used widely in healthcare, with evidence that it can improve clinical outcomes and be associated with a positive safety culture. Our aim was to explore the impact of introducing this type of training to a gynaecological team. Methods: In this interrupted time-series study, 'Safety Attitudes Questionnaire' (SAQ) data was collected both before and after SBMPTT was introduced to a gynaecological team. Results: Low baseline SAQ scores coincided with difficulty in establishing the training, meaning that at the end of our study period only a small proportion of staff had actually attended a training session. Despite trends towards improvement in scores for safety climate, teamwork climate and job satisfaction, no statistically significant difference was observed. There was however an improved perception of the level of collaboration between nursing staff and doctors after the introduction of training. Conclusions and Discussion: In this paper we explore a hypothesis that low baseline SAQ scores may highlight that the multiprofessional teams most in need of training work in environments where it is more challenging to implement. There is evidence from other specialties that multiprofessional team training works, now we need to understand how to address the barriers to getting it started. In this paper we suggest how the SAQ could be used as a directive tool for improvement; using the detailed analysis of the local safety culture it provides to both inform future training design and also provide management with an objective marker of progress.